BASIC SCHOOL AS THE IMPORTANT STAGE OF FORMING OF INFORMATIVE SPECIALIST`S COMPETENCE. - V. Efimenko (Kherson State University, 2010)
The following article deals with a problem of forming of informative pupil's competence.